2002
DOI: 10.1021/ja0274406
|View full text |Cite
|
Sign up to set email alerts
|

(π-Allyl)palladium Complexes Bearing Diphosphinidenecyclobutene Ligands (DPCB):  Highly Active Catalysts for Direct Conversion of Allylic Alcohols

Abstract: The (pi-allyl)palladium complex bearing an sp2-hybridized phosphorus ligand (DPCB-OMe: 1,2-bis(4-methoxyphenyl)-3,4-bis[(2,4,6-tri-tert-butylphenyl)phosphinidene]cyclobutene) efficiently catalyzes direct conversion of allylic alcohols in the absence of activating agents of alcohols such as Lewis acids. N-Allylation of aniline proceeds at room temperature to afford monoallylated anilines in 90-97% yields. C-Allylation of active methylene compounds is also successful at 50 degrees C using a catalytic amount of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
140
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(147 citation statements)
references
References 28 publications
(10 reference statements)
2
140
0
5
Order By: Relevance
“…Recent advances in this field are based on the use of transition metal complexes as catalysts. Remarkable are the Ru-, [3] Re-, [4] and Au-catalyzed [5] propargylation of nucleophiles with propargylic alcohols, the Tsuji-Trost reaction of allylic alcohols with active methylene compounds, [6] the reaction of secondary benzylic alcohols with different nucleophiles catalyzed by La, Sc, or Hf salts, [7] and the Fe-, or Au-catalyzed arylation of benzylic alcohols.[8] In addition, InCl 3 has emerged as a powerful catalyst to perform direct nucleophilic substitution of allylic and benzylic alcohols. [9] Although the catalytic activation of alcohols is thought to be difficult due to the poor leaving ability of the OH group, we have recently found that simple Brønsted acids like p-toluenesulfonic acid monohydrate (PTS) catalyze the direct nucleophilic substitution of propargylic alcohols.…”
mentioning
confidence: 99%
“…Recent advances in this field are based on the use of transition metal complexes as catalysts. Remarkable are the Ru-, [3] Re-, [4] and Au-catalyzed [5] propargylation of nucleophiles with propargylic alcohols, the Tsuji-Trost reaction of allylic alcohols with active methylene compounds, [6] the reaction of secondary benzylic alcohols with different nucleophiles catalyzed by La, Sc, or Hf salts, [7] and the Fe-, or Au-catalyzed arylation of benzylic alcohols.[8] In addition, InCl 3 has emerged as a powerful catalyst to perform direct nucleophilic substitution of allylic and benzylic alcohols. [9] Although the catalytic activation of alcohols is thought to be difficult due to the poor leaving ability of the OH group, we have recently found that simple Brønsted acids like p-toluenesulfonic acid monohydrate (PTS) catalyze the direct nucleophilic substitution of propargylic alcohols.…”
mentioning
confidence: 99%
“…Alternatively they can be activated by stoichiometric Lewis acid adducts, such as BEt3 and Ti(O-i-Pr)4 [4][5][6][7][8][9][10][11][12][13][14]. However, all OPEN ACCESS these approaches lead to formation of substantial (in most cases stoichiometric) amounts of (salt) waste, which can be avoided by the direct catalytic activation of the allylic alcohol [15][16][17][18][19]. Ozawa and co-workers reported the first examples in which allylic alcohols were directly used as coupling partners in Pd-catalyzed allylic substitution reactions by the π-allyl palladium complexes of substituted diphosphinidenecyclobutene ligands (DPCB-Y) [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, all OPEN ACCESS these approaches lead to formation of substantial (in most cases stoichiometric) amounts of (salt) waste, which can be avoided by the direct catalytic activation of the allylic alcohol [15][16][17][18][19]. Ozawa and co-workers reported the first examples in which allylic alcohols were directly used as coupling partners in Pd-catalyzed allylic substitution reactions by the π-allyl palladium complexes of substituted diphosphinidenecyclobutene ligands (DPCB-Y) [15]. Mechanistic studies demonstrated that C-O bond dissociation is the rate-determining step in these reactions (proposed by Ozawa and Yoshifuji to proceed via a palladium-hydride intermediate) [20], which was later also confirmed by le Floch and co-workers on the basis of DFT calculations (invoking ammonium promoted protonation of the allyl alcohol) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Pt(COD)Cl 2 , bis[2-(diphenylphosphino)phenyl ether in dioxane (11) or HgOÁHBF 4 in THF (12). There are few reports on the N-allylation reaction using palladium complex catalyst, for example 1,2-(p-MeOC 6 H 4 ) 2 cyclobuten[0 P(2,4,6-tri-t-BuPh)] 2 PdOTf in toluene (13), Mo 3 PdS 4 (14), Pd ×Et 3 B (15), Ti(O-iPr) 4 Pd(OCOCF 3 ) 2 -dppb in benzene (16), and Pd{P(OC 6 H 5 ) 3 } 4 in toluene (17). There is also a recent report on N-allylation of amines using silica as a heterogeneous catalyst (18).…”
mentioning
confidence: 99%